OP0326 Modelling the interaction between disease microenvironment and mesenchymal stem cells in scleroderma. (12th June 2018) - Taki, Z.; Abdi Ahmed, B.; Gostjeva, E.; Venturini, C.; Denton, C.; Salama, A.; Lopez, H.; Stratton, R.
Abstract : Background: Mesenchymal stem cells (MSCs) are pleuripotent bone marrow and tissue resident cells implicated in homeostasis and tissue repair. Systemic sclerosis (scleroderma, SSc) is a severe connective tissue disease characterised by progressive fibrotic thickening of the dermis, accompanied by loss of subcutaneous fat and microvasculature. Aberrant activation of MSCs within the disease microenvironment may underly the persistent fibrotic repair process, or account for the failure of adipogenesis and dysregulated vascular repair. Objectives: We sought to: 1) determine whether activated MSCs are present within the SSc involved skin lesions, 2) test whether SSc suction blister fluid (BF) derived from involved forearm skin can induce phenotype changes in MSCs, 3) fully profile the altered gene expression in MSCs exposed to SSc BF, 4) investigate the role of key factors present at increased level in SSc BF (IL-31, lactate). Methods: Novel post-fixation collagenase tissue dissociation techniques applied to 1 mm tissue sections, combined with Feulgen staining of DNA, were used to identify MSCs undergoing metakaryotic division within the involved skin of SSc patients. Fat derived MSCs from healthy controls were treated in tissue culture with blister fluid derived from the fibrotic skin lesions or from matched sites in healthy individuals, or exposed to key constituent factors, including cytokines (IL-31, 50 ng/ml), metabolites (lactate, 25 mM), and enhanced stiffness matrix (50 kPa gels). The responses of MSCs were studied by analysis of next generation sequencing (NGS) and phenotype changes. Results: MSCs undergoing metakaryotic division were identified in SSc skin biopsy material but not in healthy control (HC) tissue (SSc vs HC, superficial dermis 0 vs 0, mid dermis 1.1 vs 0 p<0.0001, deep dermis 1.4 vs 0 p<0.0001 metakaryotic cells per x20 field). SSc BF (diluted 1:125 in media) induced disease-relevant phenotype changes in MSCs, such as αSMA expression (p<0.05), collagen gel contraction (p<0.002) and scratch wound repair (p<0.016), as well as loss of adipogenic potential, more than control BF or media alone, due in part to elevated IL-31 and lactate. NGS indicated that SSc blister fluid induced treatment-specific gene expression in MSCs (figure 1), more differentially than in normal dermal fibroblasts, consistent with activation of fibrosis, wound repair, migration, osteogenesis, connective tissue formation and loss of angiogenesis/vascular repair. Induction of αSMA in MSCs was dependent on the matrix stiffness in model systems. Conclusions: Factors present at elevated levels in the disease microenvironment, including cytokines and metabolites, as well as the stiffened ECM, are capable of promoting the migration and differentation of fat derived MSCs, towards tissue reparative cells implicated in the fibrotic process. Conversely, the adipogenic and vascular regenerative potential of these cells may be reduced by exposure to the SSc microenvironment. Disclosure of Interest: None declared